A necessária limitação da justiça constitucional no Brasil: hermenêutica filosófica gadameriana e atuação do Supremo Tribunal Federal - Gundim, Wagner Wilson Deiró (2020)
This study aims to propose the adoption of Gadamer's philosophical hermeneutics as a formula to improve the performance of the Federal Supreme Court as the main body to safeguard the prevalence of constitutional norms, strengthening the spirit brought by the Federal Constitution. It adopts deductive and inductive methods as its scientific methodology, since the analyses fall as much on the theoretical-normative structure of the analyzed institutes as their application in the practical field, in addition to the hypothetical-dialectic method, since based on the thesis and antithesis of the themes discussed it proposes a new synthesis (vision) on the need to improve Constitutional Justice in Brazil. To better understand the theme, it initially analyzes the theoretical contours of Constitutional Justice, approaching its definition, its functions, the existing models and its legitimacy from the democratic formula to, in the sequence, deal specifically with the evolution and performance of the Supreme Court as the highest body in the exercise of constitutional justice. Therefore, in order to give a practical perspective of the problem raised, it moves towards an analysis of recent trials of the Supreme Court, which apparently demonstrate the tension between the hermeneutical exercise constitutionally appropriate and possible subjectivist decisions at the time of making the decision, such as the decision that made possible the anticipation of the effects of the res judicata and imprisonment after a confirmatory decision issued by a collegiate body, the granting of erga omnes effectiveness to the decisions rendered in the diffuse control of constitutionality, nullifying the resolutive task of the Federal Senate, as well as the decisions that, respectively, restricted the constitutional immunity guaranteed to deputies and senators and created a new thesis regarding the limitation to the exercise of positions in the line of succession of the Presidency of the Republic by persons being investigated before the Supreme Court. It also analyzes the main currents regarding the basis of judicial interpretation, such as the objective and subjective views of the act of interpreting, focusing on the theories of Hans Kelsen, Herbert Hart and Carl Schmitt, as well as argumentative theories, such as that of Robert Alexy. He investigates, in the final topic, the Gadamerian philosophical hermeneutics and points out its main theories in order to suggest, in conclusive lines, the adoption of the dialogical philosophical hermeneutics, which mixes Gadamer's philosophy and the institute of dialogue between judges as an important instrument in the improvement of the performance of the Supreme Court and the strengthening of its performance as an essential organ in the democratic context of the contemporary world